2016
DOI: 10.1123/jcsp.2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Body Image in Athletes With Physical Disabilities

Abstract: The purpose of this study was twofold: (a) to explore the body image of athletes with physical disabilities, and (b) to understand how sport influences body image among these athletes. We interviewed 20 male and female athletes (Mage = 34.25, SD = 8.49) from a variety of sports regarding their body image and the role of sport in influencing body image. A thematic analysis (Braun & Clarke, 2006) was used to generate six themes: (a) personal significance of injury and disability, (b) noncentrality of the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…It could be argued that an athlete's desires to colour or decorate their prosthesis in this way denoted their achievements, status or image and therefore reinforced the behaviour and existence of self-decoration described in this papers background section. This compliments observations seen from those who participate in competitive sport with a disability [16] and concerns over how they are perceived by others [17]. However, it is not clear in these studies if the prosthesis is seen as an extension of their physical form or merely an independent entity or artefact that is separate to it.…”
Section: "It Reminds Me When I Saw the Para-cycling Events On The Velsupporting
confidence: 75%
See 2 more Smart Citations
“…It could be argued that an athlete's desires to colour or decorate their prosthesis in this way denoted their achievements, status or image and therefore reinforced the behaviour and existence of self-decoration described in this papers background section. This compliments observations seen from those who participate in competitive sport with a disability [16] and concerns over how they are perceived by others [17]. However, it is not clear in these studies if the prosthesis is seen as an extension of their physical form or merely an independent entity or artefact that is separate to it.…”
Section: "It Reminds Me When I Saw the Para-cycling Events On The Velsupporting
confidence: 75%
“…However, with other forms of sports equipment such as tennis balls [14] and footballs [15], athletes have been shown to exhibit emotionally led perceptions of them. In addition, the athletes' body-image has been proposed to be an integral part of a sportsperson with limb absence psyche and wellbeing [16]. Therefore, the contribution that the visual appearance of a prosthetic limb has could potentially also be seen of crucial importance to para-athletes.…”
Section: Athletes and Prosthetics Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Holzer et al ( 2014 ) identified amputation as a source of lower body image. LTPA participation improved body image in amputees and generated pride in the way they looked (Galli et al, 2016 ; Wetterhahn et al, 2002 ). Inadequate or absent goal setting has been shown to pose a barrier to LTPA among lower extremity amputees (Batten et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most research on eating disorders in sport and dance has focused on Caucasian female collegiate or elite competitors. Thus, with a few exceptions (e.g., Galli, Reel, Henderson, & Detling, 2016), the experiences of athletes and dancers from marginalized groups (e.g., people with disabilities, people of color) have been largely ignored in recognizing and overcoming this condition. Researchers must focus on minority groups, if theoretical models and interventions are to best serve all athletes and dancers-not just those competitors representing the majority.…”
Section: Priority Areas For Future Researchmentioning
confidence: 99%